Efficiency of Islamic and conventional banks in Malaysia - Farhana, Ismail; M. Shabri, Abd. Majid; Rossazana, Ab. Rahim (Emerald Group Publishing Limited, 2013)
Purpose – The main purpose of this paper is to examine cost efficiencies of the selected Islamic and conventional commercial banks over the period of 2006 to 2009 in Malaysia. Design/methodology/approach – Data envelopment analysis (DEA) was initially used, to investigate the cost efficiency of the Malaysian banking sector and followed by Tobit regression analysis determine factors influencing the efficiency of Islamic and conventional banks in Malaysia. Findings – The DEA results reveal technical efficiency as the main contributor of cost efficiency for conventional commercial banks and allocative efficiency as the main contributor for cost efficiency of Islamic commercial banks. This indicates conventional commercial banks have been efficient in utilizing information technology and electronics. Islamic commercial banks conversely have been efficient in allocating and utilizing their resources. Additionally, scale efficiency is found to be the main source of technical efficiency for both Islamic and conventional commercial banks, denoting that size is important in improving bank efficiency. The results of Tobit regression analysis are twofold. First, it documents capitalization and bank sizes are positively and significantly associated to efficiency. Secondly, loan quality is found to be negatively and significantly associated to efficiency. Originality/value – This paper contributes to the body of knowledge through its literature discussions on the efficiency of both Islamic and conventional banks and the effect of banks’ specific characteristics on their efficiency.